(untitled) (University of Khartoum Engineering Journal, 2022)
The aim of this paper is to develop empirical relationship between CBR values and soil index propertiesof cohesive soils as road subgrade. However; it is always difficult for highway engineers to obtain representativeCBR values for design of pavement. Over the years, many correlations had been proposed by various researchersin which the soil index properties were used to develop these correlations. The CBR value is affected by the initialstate parameters of soil as described by the water content and dry density and the testing conditions. Silty clay soilsamples were compacted at different water contents and dry densities to measure the strength by CBR tests insoaking and unsoaking conditions. The results show that the CBR values of these soils are greatly influenced bythe water content and dry density (i.e. the initial state parameters) of the soil as well as the testing conditions.Analysis of the experimental data indicated that it is possible to combine these initial state parameters in a wayreflecting the influence of each of them on the CBR. Therefore a new concept has been developed; this is calledthe initial state factor. This factor is also developed for the soaking or saturated condition and is called the soakingstate factor. On basis of this concept, a reliable strong correlation has been established between CBR values andsoil state factors and plasticity index. Comparison between the measured soaked or unsoaked CBR values and thecalculated results using the developed equations clearly indicates the reliability of these equations